Microfinance in Africa : Experience and Lessons From Selected African Countries - Blavy, Rodolphe (IMF Working Papers; Working Paper ;, 2004)
Based on the experience of selected countries, this paper offers a critical presentation of the development of the microfinance sector in Africa. The paper supports the view that microfinance institutions, especially those engaged in full financial intermediation, complement effectively the banking sector in extending financial services and successfully draw on the rich experience of community-based development and preexisting informal methods of financial intermediation in Africa. Growing linkages between microfinance institutions and the banking system and the dissemination of good practices by nongovernment organizations contribute to the sound development of the sector, supported by regulation and supervision by local authorities.